Evaluating the Medical Symptom Validity Test (MSVT) in a Sample of Veterans Between the Ages of 18 to 64. Issue 2 (4th March 2017) - Reslan, Summar; Axelrod, Bradley N.
ABSTRACT: The purpose of the current study was to compare three potential profiles of the Medical Symptom Validity Test (MSVT; Pass, Genuine Memory Impairment Profile [GMIP], and Fail) on other freestanding and embedded performance validity tests (PVTs). Notably, a quantitatively computed version of the GMIP was utilized in this investigation. Data obtained from veterans referred for a neuropsychological evaluation in a metropolitan Veteran Affairs medical center were included ( N = 494). Individuals age 65 and older were not included to exclude individuals with dementia from this investigation. The sample revealed 222 (45%) in the Pass group. Of the 272 who failed the easy subtests of the MSVT, 221 (81%) met quantitative criteria for the GMIP and 51 (19%) were classified as Fail. The Pass group failed fewer freestanding and embedded PVTs and obtained higher raw scores on all PVTs than both GMIP and Fail groups. The differences in performances of the GMIP and Fail groups were minimal. Specifically, GMIP protocols failed fewer freestanding PVTs than the Fail group; failure on embedded PVTs did not differ between GMIP and Fail. The MSVT GMIP incorporates the presence of clinical correlates of disability to assist with this distinction, but future research should consider performances on other freestanding measures of performance validity to differentiate cognitive impairment from invalidity.